LEADERSHIP AND MANAGERIAL COMPETENCE - I.M, Arzimatova (Journal of Learning on History and Social Sciences, 2025)
Objective: This study examines the theoretical foundations and practical implications of leadership effectiveness and managerial competence within the evolving socio-political and economic context of Uzbekistan. Method: Utilizing a qualitative, socio-philosophical approach, the research integrates content analysis of theoretical literature, policy documents, and leadership models, with a focus on transformational and servant leadership paradigms. Results: The findings reveal that effective leadership extends beyond personal charisma or formal authority, requiring a synthesis of strategic thinking, ethical grounding, continuous learning, and adaptability to technological and cultural changes. Leadership effectiveness is shown to be deeply influenced by institutional systems and cultural values. Novelty: This study contributes a culturally resonant and future-oriented leadership model tailored to Uzbekistan’s modernization efforts, emphasizing the integration of national perspectives with global leadership theories. It highlights the urgency of developing practical frameworks for leadership training, strategic management, and moral responsibility, aligning local leadership development initiatives with international standards